Our Experience in Carotid Endarterectomy. A Retrospective Study - Edmond Nuellari; Edvin Prifti (Albanian Journal of Trauma and Emergency Surgery, 2024)
Introduction: Carotid endarterectomy (CEA) operations have been more frequent in our practice in recent years, primarily for asymptomatic patients. In this article, we present our experience in this field.